2020
DOI: 10.1111/pace.14038
|View full text |Cite
|
Sign up to set email alerts
|

Time‐ and frequency‐domain analysis of repolarization phase during recovery from exercise in healthy subjects

Abstract: Background/aim: Recently, data from temporal dispersion of myocardial repolarization analysis have gained a capital role in the sudden cardiac death risk stratification. Aim of this study was to evaluate the influence of heart rate, autonomic nervous system, and controlled breathing on different myocardial repolarization markers in healthy subjects. Method: Myocardial repolarization dispersion markers from short-period (5 minutes) electrocardiogram (ECG) analysis (time and frequency domain) have been obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…We believe sympathetic hyperactivity and neurohumoral activation could influence the Te and TeSD. In previous studies, it was reported that sympathetic activation during exercise was able to induce an increase in Te and TeSD in normal subjects [50]. In animal models, we observed an increase in the short-term variability of the Te interval during pacinginduced acute congestive heart failure and experimental acute myocardial ischemia [35,51].…”
Section: Discussionsupporting
confidence: 59%
“…We believe sympathetic hyperactivity and neurohumoral activation could influence the Te and TeSD. In previous studies, it was reported that sympathetic activation during exercise was able to induce an increase in Te and TeSD in normal subjects [50]. In animal models, we observed an increase in the short-term variability of the Te interval during pacinginduced acute congestive heart failure and experimental acute myocardial ischemia [35,51].…”
Section: Discussionsupporting
confidence: 59%
“…result is a prolonged temporal dispersion of QT and Te. [14][15][16][17] Recent observations have highlighted that sympathetic hyperactivity is able to induce an increase in QTe variability index, QTeVN, TeVN, TeSD, in normal 17 and pathological 23,24 conditions. Thus, the morphological and structural alterations of the myocardium resulting in specific modifications of these electrocardiographic markers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, sodium, calcium, and potassium channels and transport mechanisms are upset in CHF 22 and the final result is a prolonged temporal dispersion of QT and Te. 14 , 15 , 16 , 17 Recent observations have highlighted that sympathetic hyperactivity is able to induce an increase in QTe variability index, QTeVN, TeVN, TeSD, in normal 17 and pathological 23 , 24 conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations